PENYELESAIAN SENGKETA PENAMBANGAN GALIAN GOLONGAN C DI KECAMATAN CEPOGO KABUPATEN BOYOLALI - Widodo, Sudiyo (MAGISTRA, 2015)
Boyolali District is an area rich in minerals, especially minerals mining group C. Sand and stone mining activities in the District of Cepogo the advantage of employment and contribution to the local government. However, the presence of mining is also causing problems, such as the convenience of surrounding communities to be disturbed. This is what then caused disputes among the people with sand miners in the subdistrict Cepogo Boyolali district. The research objective is (1) To determine disputes arising from mining excavation category C in subdistrict Cepogo Boyolali district. (2) To determine the existence of dispute resolution efforts against mining excavation in the Sub-category C subdistrict Cepogo Boyolali district. (3) To determine the dispute resolution model category C mining excavation in the future in the subistrict Cepogo Boyolali district. Approximation method used is non-doctrinal or empirical. This type of research is a qualitative descriptive study. Source data used are the primary data and secondary data. Techniques of data collection through interviews and documentation studies. The data analysis technique is interactive analysis. The results showed that (1) Disputes arising from mining excavation category C in subdistrict Cepogo Boyolali District originated from any breach of licensing mechanism to mine where the miners are not transparent in conducting its mining activities causing impacts to the surrounding community such as noise, damage to rural roads and the destruction of water catchment areas. (2) Resolution of disputes mining excavation in the Sub-category C Cepogo Boyolali District by way of mediation. But the dispute over the issue of mining quarrying category C has not been completed. Therefore, in order to provide legal certainty for communities in the District Cepogo, Boyolali District Government issued a decision on the mining of minerals C. The decision is set forth in Decree No. 545/05082/05/2010 Boyolali Regent Policy Gedangan Village C Mining and Quarrying Wonodoyo Village, District Cepogo. (3) The model dispute resolution mining excavation Group C in the future, especially in the District Boyolali would be better to use a means of dispute resolution outside the court. Keywords: Settlement of Disputes, Minerals Mining Group C.